(3GdfbhO h GdeUGQa h GdfXQjI GdfbOjI (B/s - (3GdLfGHj, gjd YLej Lejds; (3QeRj jGSjf jSY, GQSdGf s ((3YeGf(B: s (3OGQ hGFd(B, s, 2008)
(3fTCI GdfbhO , GdbhGYO GdfbOjI , YQV GdfbO h GdYhGed GdeDKQI ajg , SQYI JOGhd GdJbhO h GdYhGed GdeDKQI ajg , GdfbhO h GdSjhdI h GdKQhI , GdHfhc GdJLGQjI h eaghegG h OhQgGaj GdhSGWI GdeGdjI , OhQ GdHfhc GdJLGQjI aj GdJCKjQ Ydi GdhOGFY , GdHfhc GdeQcRjI , GdfXQjI GdfbOjI GdcdGSjcjI , HfGA GdfXQjI GdcdGSjcjI aj GWGQ fXQjI GdeYGedGJ , GdGacGQ GdLOjOI aj CKQ GdfbhO Ydi GdfTGW GdGbJUGOj , GdJMdjd GdfjhcdGSjcj ddfbhO (B((3fXQjI GdGQUOI GdfbOjI (B) (3, OhQ GdfbhO aj GdfTGW GdGbJUGOj aj Xd GdGacGQ GdcjfRjI h GdfXQjI GdcejI GdLOjOI, GdWdH Ydi GdfbhO aj GWGQ GdJMdjd GdcdGSjcj h GdfjhcdGSjcj , OhGaY GdWdH YdiGdfbhO YfO GdfXQjI GdcjfRjI , GdfXQjI GdfbOjI GdeYGUQI dcejI GdfbhO , GdSjGSI GdfbOjI h CgOGagG h COhGJgG , GdJVNe(B.s
((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdCfXeI GdfbOjIs; (3GdeUGQas; (3GdfbhOs